Hubungan durasi penggunaan gadget dengan kualitas tidur pada remaja SMA - Ani Ani; Suratini Suratini; Tiwi Sudyasih (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Sleep quality is an important factor in maintaining adolescents’ physical, psychological, and academic well-being. The increasing use of digital gadgets among high school students may negatively affect sleep patterns and quality, particularly due to nighttime screen exposure. Purpose: To determine the relationship between the duration of gadget use and sleep quality among students of SMA. Method: This study employed a quantitative descriptive correlational design with a cross- sectional approach. The sample consisted of 57 tenth-grade students selected using simple random sampling. Data were collected using a gadget usage duration questionnaire and the Pittsburgh Sleep Quality Index (PSQI). Data analysis was conducted using the Spearman Rank correlation test with a significance level of α = 0.05. Results: The majority of respondents had high levels of gadget usage (74%) and poor sleep quality (88%). Spearman correlation analysis revealed a significant relationship between gadget usage duration and sleep quality (p = 0.001; r = 0.156). The correlation was weak but positive, indicating that longer gadget usage was associated with poorer sleep quality. Conclusion: There is a significant relationship between gadget usage duration and sleep quality among students of SMA.   Keywords: Adolescents;  Gadget Usage Duration; PSQI; Sleep Quality.   Pendahuluan: Kualitas tidur merupakan faktor penting dalam menjaga kesehatan fisik, psikologis, dan performa akademik remaja. Peningkatan penggunaan gadget pada siswa SMA berpotensi memengaruhi pola dan kualitas tidur, terutama akibat paparan layar pada malam hari. Tujuan: Untuk mengetahui hubungan antara durasi penggunaan gadget dengan kualitas tidur pada siswa SMA. Metode: Penelitian ini menggunakan desain kuantitatif dengan pendekatan deskriptif korelasional dan metode cross-sectional. Sampel berjumlah 57 siswa kelas X yang dipilih menggunakan teknik simple random sampling. Data dikumpulkan menggunakan kuesioner durasi penggunaan gadget dan instrumen Pittsburgh Sleep Quality Index (PSQI). Analisis data dilakukan dengan uji korelasi Spearman Rank dengan tingkat signifikansi α = 0.05. Hasil: Mayoritas responden memiliki durasi penggunaan gadget kategori tinggi (74%) dan kualitas tidur buruk (88%). Uji korelasi Spearman menunjukkan adanya hubungan yang signifikan antara durasi penggunaan gadget dan kualitas tidur (p = 0.001; r = 0.156) dengan tingkat keeratan hubungan lemah dan arah positif yang berarti semakin lama durasi penggunaan gadget maka semakin buruk kualitas tidur siswa. Simpulan: Terdapat hubungan signifikan antara durasi penggunaan gadget dengan kualitas tidur pada siswa SMA.   Kata Kunci: Durasi Penggunaan Gadget; Kualitas Tidur; PSQI; Remaja.